(untitled) (Universal International Scientific Journal, 2026)
This article examines the development of financial responsibility in primary school children within a family-based environment. It substantiates the relevance of economic education for primary school children in the context of contemporary socioeconomic changes. It explores the concept of "financial responsibility" and analyzes the role of the family as the primary environment for developing economic understanding and skills for rational financial management. Pedagogical conditions and effective methods for developing financial responsibility in primary school children are identified. The need for coordinated interaction between family and school in developing the foundations of financial literacy is emphasized. The results of the theoretical analysis allow us to identify key areas for improving family economic education.